Lessons from the Southern enlargement of the EU for the environmental dimensions of Eastern enlargement in particular for Poland - Onno J. Kuik; Frans H. Oosterhuis (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper analyses the environmental dimensions the past accession of Greece, Portugal and Spain to the EU in order to draw lessons for the current accession of countries of Central and Eastern Europe. A distinction is made between scale, composition and technique effects. Two major conclusions are drawn. First, the impacts of accession differed significantly among accession countries, due to economic, social, political and and geographical factors. Second, the composition effect was relatively unimportant and the technique effect was positive due to the modernisation of production and the implementation of the environmental acquis. A negative scale effect dominated in the areas of consumption and transport. Accession also led to growing disparities at the regional level. At the time of accession, Greece, Portugal and Spain showed similarities with present-day Eastern European countries. Lessons from the southern enlargement are drawn for the current accession, in particular for Poland.
Keywords: F15; F18; Q20; 330; EU enlargement; environment; EU-Erweiterung; Umwelt; Umweltbelastung; Griechenland; Spanien; Portugal; Polen; EU-Staaten